Pembatalan Akta Jual Beli Tanah Atas Dasar Perbuatan Melawan Hukum Berdasarkan Putusan Pengadilan (Studi Kasus Putusan Pengadilan Tinggi Denpasar Nomor 63/PDT/2020/PT.DPS) - Marito, Bintang; Tony, Tony; Agustining, Agustining; Ketaren, Marianne Magda (Mahesa Research Center, 2023)
This research uses a normative juridical approach method, with the data used is secondary data, namely data that supports information or supports the completeness of Primary Data obtained from libraries and the author's personal library collection carried out by means of library or literature studies. Data analysis used normative analysis, that is, the collected data is expressed in the form of a logical and systematic description, then analyzed to obtain clarity in solving the problem, then conclusions are drawn deductively, namely from general matters to specific matters. Based on the results of the research, it can be seen that the validity of the Deed of Sale and Purchase Number 619/2012 is considered to be legally flawed in subjective terms because of fraud or engineering fraud, mistakes, lies or deception is related to to whom the sale and purchase transaction of the disputed object should be carried out. The result is that the transfer of the Certificate of Ownership Number 2636/Sukawati Village is declared invalid and does not have binding legal force, so in this case the Plaintiffs are still the legal owners of the disputed object.